Juridical Analysis of the Legal Force of Birth Certificates Issued by Healthcare Professionals - S.Sianturi; T.Tambunan (The Medical Journal of Hospital Management and Health Law, 2025)
Introduction: A birth certificate is a crucial legal document that establishes an individual's civil status and citizenship. In practice, healthcare professionals often issue preliminary birth statements or, in some administrative variations, facilitate the direct issuance of birth records, raising questions about the boundaries of their legal authority. This study addresses this phenomenon by examining the formal legal strength of such documents. Methods: This research employs a normative juridical method, analyzing statutory legislation, secondary legal materials, and comparative jurisprudence regarding civil registration. Results: The findings indicate that while healthcare professionals possess the authority to issue medical statements of birth (surat keterangan lahir), they do not hold the statutory power to issue official birth certificates (akta kelahiran), which remains the exclusive domain of civil registration authorities. Documents issued beyond this scope lack the evidentiary power of authentic deeds. Discussion: The legal force of documents issued by healthcare professionals is limited to that of private deeds or administrative evidence rather than absolute authentic proof. A comprehensive literature review indicates that confusing medical verification with civil registration compromises legal certainty, creating a research gap regarding the precise liability of healthcare workers who exceed their administrative boundaries. Conclusions: Healthcare professionals cannot legally issue birth certificates; their role is strictly evidentiary within the medical spectrum. It is recommended that governments streamline the integration between healthcare facilities and civil registries without blurring their distinct legal authorities.